The study of the relationship between food additives and the childhood asthma based on metabolome analysis - Chen, Mingcong; Xu, Xinfeng; Jiang, Xinyao; Hui, Jinyan; Tao, Xuna; Bao, Yuling; Cao, Shuyuan; Wu, Qian (Frontiers in Immunology, 2025)
BackgroundEpidemiological evidence suggests health risks arise from intake of food additives. This study aims to investigate the mechanisms linking food additives to childhood asthma through a metabolomics strategy.MethodsA total of 120 children with asthma and 120 control subjects were recruited. Serum concentrations of ten food additives - including cyclamate, neotame, aspartame, sodium saccharin, acesulfame, sucralose, benzoic acid, dehydroacetic acid, sunset yellow, and ponceau 4R - were quantified using UPLC-MS/MS. The associations between food additives and asthma were evaluated by logistic regression and chi-square tests. Serum metabolic profiling was performed by UPLC-MS. Identified asthma-associated metabolites were subsequently analyzed for pathway enrichment and mediation effects. In murine studies, acesulfame, sodium saccharin, sodium benzoate, or their mixtures were co-administered with OVA to C57BL/6 mice. Airway inflammation, IgE, IL-4, IL-17A, immune cell differentiation, and CD4+ T cell metabolomics profiles were assessed.ResultsThe detection rates for dehydroacetic acid, benzoic acid and sodium cyclamate exceeded 60%. Benzoic acid, dehydroacetic acid and acesulfame were significantly associated with asthma. Mediation analysis identified fourteen metabolites as mediators in the relationship between benzoic acid and dehydroacetic acid, and childhood asthma, including PC(14:0/14:0), LysoPC(17:0), glycerophosphocholine, PC(18:1(9Z)e/2:0), PE(18:2(9Z,12Z)/14:0), glutamic acid, glutamine, GlcCer(d18:1/16:0), sphingosine, sphingosine-1-phosphate, spermine, spermidine, histidine, and acetylcholine. These metabolites were enriched in glycerophospholipid metabolism, β-alanine metabolism, glutathione metabolism, sphingolipid metabolism, arginine and proline metabolism, arginine biosynthesis, and histidine metabolism pathways. In murine models, food additives significantly exacerbated lung tissue inflammation and elevated levels of IgE, IL-4, and IL-17A in both BALF and serum, and also increased eosinophil percentages in BALF. Furthermore, flow cytometry showed significant alterations in Th1/Th2, Th17/Treg and allergic DC/tolerogenic DC balance within the mesenteric lymph node (MLN) and the lung tissue. Metabolomic profiling of CD4+ T-cells from the MLN demonstrated that food additives primarily disrupted phenylalanine, tyrosine, and tryptophan biosynthesis, and glycerophospholipid metabolism pathways. This disruption involved key metabolites including PC(36:4), platelet-activating factor, LysoPE(P-16:0), PS(14:0/5-iso PGF2VI), PE(14:1(9Z)/15:0), Na,Na-dimethylhistamine, docosadienoic acid, cyclohexaneundecanoic acid, L-acetylcarnitine, phosphorycholine, Cer(d18:2/20:0), DG(22:1n9/0:0/20:4n6), 5’-methylthioadenosine, L-tyrosine, and N-palmitoyl leucine.ConclusionFood additives may aggravate asthma by metabolically dysregulating the homeostasis of helper T-cells and antigen-presenting cells, thereby disrupting immune tolerance.